Phylogenetic Group Distribution of Uropathogenic Escherichia coli and Related Antimicrobial Resistance Pattern: A Meta-Analysis and Systematic Review - Halaji, Mehrdad; Fayyazi, Amirhossein; Rajabnia, Mehdi; Zare, Donya; Pournajaf, Abazar; Ranjbar, Reza (Frontiers in Cellular and Infection Microbiology, 2022)
The phylogenetic classification of Escherichia coli isolates is of great importance not only for understanding the populations of E. coli but also for clarifying the relationship between strains and diseases. The present study aimed to evaluate the prevalence of phylogenetic groups, antibiotic susceptibility pattern, and virulence genes among uropathogenic E. coli (UPEC) isolated from different parts of Iran through a systematic review and meta-analysis. Several international electronic sources, including Web of Science, PubMed, Scopus, and Embase, were searched (2000–2020) in order to identify the studies compatible with our inclusion criteria. The meta-analysis was performed using the metaprop program in the STATA (version 11) software. Based on our comprehensive search, 28 studies meeting the eligibility criteria were included in the meta-analysis. The pooled prevalence of phylogroups B2, D, B1, and A was 39%, 26%, 18%, and 8%, respectively. In addition, there was a significant heterogeneity among different phylogroups. However, according to the results of Begg’s and Egger’s tests, there were no significant publication bias in phylogroups B2, D, B1, and A. This research provided the first comprehensive study on phylogroups of UPEC isolated in Iran. Our findings indicated that phylogroup B2 and group D were the most predominant phylogenetic groups among UPEC isolates in various regions of Iran. In addition, we observed that certain phylogenetic groups are more antibiotic resistant than the others. It was also observed that the dissemination of virulent phylogroup B2 and D should be controlled via comprehensive infection control measures. Additionally, certain strategies should be developed for monitoring the antibiotic therapy.